THE INFLUENCE OF WORK ATTITUDE, WORK MOTIVATION, JOB SATISFACTION, AND COMPENSATION ON EMPLOYEE PERFORMANCE - Erlinda, Dessy; Norfiana, Lita; Jatmika, D (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Employee performance is influenced by work attitude, work motivation, job satisfaction, and compensation applied to employees of PT Banua Alam Semesta Banjarmasin using a quantitative approach. This research is explanatory research. The research population was 53 employees. The sampling technique used saturated or total sampling. Data collection used a questionnaire. The data analysis technique used regression analysis. The results of data analysis show that work attitude, work motivation, job satisfaction, and compensation have a partial effect on the performance of PT Banua Alam Semesta Banjarmasin. Work attitude has an effect on employee performance because 0.024 < 0.007. Work motivation has an effect on employee performance because the significance is 0.047 < 0.05. Job satisfaction has an effect on performance because the significance is 0.028 < 0.05. Compensation has an effect on performance because the significance is 0.000 < 0.05. Work attitude, work motivation, job satisfaction, and compensation have an effect on the performance of PT Banua Alam Semesta Banjarmasin simultaneously. It is recommended that employee performance be improved by improving work attitude, work motivation, job satisfaction, and compensation. Keywords: Work Attitude, Work Motivation, Job Satisfaction, Compensation, and Performance